O estado de pobreza nas relações de consumo: os direitos humanos na proteção dos consumidores hipervulneráveis - Freitas, Denilson de Souza (2023)
The precepts of human rights justified the implementation of the consumer protection system, a fragile part of the contractual relationship and, therefore, vulnerable to the supplier of goods and services. However, the state of poverty experienced by a large part of the Brazilian population also provides weakness. Thus, the hypothesis of aggravation of the vulnerability of the consumer in poverty in the contractual relationship arises. The objective of the present work is to analyze the participation of the person in a state of poverty in consumption relations and its consequences. Through the national and foreign bibliographic collection, in a qualitative way, and guided by deductive method, the work is inaugurated with a propaedeutic approach of the influences of policy and ideology in the historical construction of human rights. Afterwards, the inherent vulnerability of consumers is analyzed from the perspective of human rights. Likewise, the state of poverty is identified as restrictions on people's capacities, a multidimensional phenomenon that leads to the hypervulnerability of poor consumers. With this conclusion, the necessary acts for the protection of disadvantaged people in consumer relations are added, both measures by the suppliers of products and services, as well as negative and provisional actions by the State, as a way of achieving substantial equality and aiming for dignified existence